2001
DOI: 10.1211/0022357011775145
|View full text |Cite
|
Sign up to set email alerts
|

The biopharmaceutical aspects of nasal mucoadhesive drug delivery

Abstract: Nasal drug administration has frequently been proposed as the most feasible alternative to parenteral injections. This is due to the high permeability of the nasal epithelium, allowing a higher molecular mass cut-off at approximately 1000 Da, and the rapid drug absorption rate with plasma drug profiles sometimes almost identical to those from intravenous injections.Despite the potential of nasal drug delivery, it has a number of limitations. In this review, the anatomy and physiology of the nasal cavity, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
168
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(179 citation statements)
references
References 103 publications
2
168
0
9
Order By: Relevance
“…According to the chemical structure of the thiolated polymer, thiolate anions are responsible for the formation of new disulfide bonds which are available at pH 6-7. Moreover, the thiolated microparticles are reported to show higher cohesive properties which are also essential for high mucoadhesion (Ugwoke et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the chemical structure of the thiolated polymer, thiolate anions are responsible for the formation of new disulfide bonds which are available at pH 6-7. Moreover, the thiolated microparticles are reported to show higher cohesive properties which are also essential for high mucoadhesion (Ugwoke et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ugwoke et al (2001) reported that polymers with thiol groups provide much higher adhesive properties than polymers generally considered to be mucoadhesive. The enhancement of mucoadhesion can be explained by the formation of covalent bonds between the polymer and the mucus layer, which are stronger than noncovalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Although intranasal drug delivery offers many advantages, one of the main limitations is the short residence time of the formulation in the nasal cavity, as a result of mucociliary clearance (MCC) 10 . This movement involves the beating of mucocilia at a frequency of 1,000 strokes per minute and hence movement of mucus of 5 mm/minute 11 .…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, the use of intelligent polymer based systems have now become more commonplace in this field and particularly the use of responsive systems which may respond to the nasal cavity temperature [13][14][15][16][17][18][19][20][21][22] or pH [23][24][25][26][27] have increased amongst researchers. Furthermore, the use of mucoadhesive polymers 4,[27][28][29][30][31][32][33] to enhance the adhesion of the formulations onto the nasal mucosa has further demonstrated the ability to prolong contact time with the mucosa and hence increase bioavailability 10,15,18,23,[34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…1,2) The nasal structure feature was one of the main biological factors. The nasal cavity could be anatomically segregated into five different regions: nasal vestibule, atrium, respiratory area, olfactory region and nasopharnyx.…”
mentioning
confidence: 99%